DETERMINATION OF COEFFICIENT OF SURFACE EFFICIENCY AT VACUUM-ATMOSPHERIC DRYING OF LARGE-DISPERSED FOOD MATERIALS IN A DENSE LAYER - B. . Abdizhapparova; N. . Khanzharov; G. . Orymbetova (Алматы технологиялық университетінің хабаршысы, 2021)
In order to take into account the actual conditions of the drying process of large-dispersed food materials located in a dense layer, having a different geometric shape, the coefficient of surface efficiency of the dried material is included into analytical description of the vacuum and atmospheric drying processes. The coefficient of surface efficiency of the dried material characterizes the ratio of the actual evaporation surface participating in the active heat and mass transfer to the total one. Experimental study of vacuum and atmospheric drying of large-dispersed materials having the shape of cube, parallelepiped and sphere at height of bulk layer 0,01-0,04 m is conducted. On the analysis of experimental data an empirical equation, allowing with a sufficient degree of reliability to take into account the actual surface evaporation, participating in active heat and mass transfer in processes of vacuum-atmospheric drying of large-dispersed food materials is obtained. The numerical values of the coefficient of surface efficiency of the dried materials with various shapes are determined.